The changes of training activity level in athletes during the COVID-19 pandemic: an analysis of self-determination motivation - Noori, Q. (Linneuniversity, 2020)
The purpose of this study was to research athlete`s training activity and motivation level for participating in sport and training during the COVID-19 pandemic crisis. Method for present research is aquestionnaire which contained instruments; a) General information about athletes; b) Training routines before & during pandemic crisis; c) Training-related motivational factors and for measuring motivation level the following questionnaires of self-determination theory were used d) SMS-2 and BREQ-2. The questionnaire was published on the internet for athletes around Sweden. Respondents were (n=160) men (n=111) and women (n=49). Result showed that athletes who continued with group training and who stopped with group training in general, have same level of motivation for the sport participation and training during the pandemic crisis. Discussion Both groups showed a reduction in the training-related variables for pre-pandemic vs during pandemic. In conclusion it showed that the athletes who continued with the group training hade better motivation level and didn`t reduced with the training frequency in contrast to the group that stopped with the group training.